Strategic manufacturing effectiveness: an empirical analysis - Al-Rasby, Ahmed Nasser (1996)
The difficulties that faced many manufacturing firms were attributed by Skinner (1969) to the inadequate attention given by top managers to the manufacturing function. He proposed a holistic framework of manufacturing strategy development that link manufacturing with corporate strategy. This work of Skinner is the first of three stages in the progression of thinking with respect to the strategic role of manufacturing as pointed out by Hum and Leow (1993). The other two stages being the demand of manufacturing to support and be consistent with corporate strategy (Wheelwright, 1978), and the present thinking that manufacturing can lead other functional areas in its contribution to the development of corporate strategy.